A case of transient ischemic attack presenting as hemichroea - Özdemir, Hasan Hüseyin; Demir, Caner F.; Taşci, Irem; Balduz, Metin (Turkish Society of Cerebrovascular Diseases, 2013)
Chorea is defined as; involuntary movements of the distal parts of limbs which have arrhythmic, rapid, bouncing or smooth, simple or complex properties. Choreiform movements occur when putamen, globus pallidus and subthalamic nucleus are affected. Chorea can be observed during the course of metabolic and vascular diseases, neurodegenerative or hereditary diseases. Chorea may be a rare symptom of cerebral hypoperfusion. Transient ischemic attack is an event that occurs in short term characterized by a temporary ischemia of brain. A wide variety of symptoms can be seen depending on the localization of cerebral hypoperfusion. Hemichorea is a very rare finding observed during transient ischemic attacks. In this article hemichorea in a case of symptomatic transient ischemic attack is discussed with relevant literature.
Hemi?kore i?le ortaya çikan geçi?ci? i?skemi?k atak olgusu
Keywords: Carotid angiography; Chorea; Transient ischemic attack